A Paradigm Shift in ELT with Artificial Intelligence: A Review on the Current State in Nepal - Bohara, Dipak Kumar (Journal of NELTA Gandaki, 2024)
Artificial intelligence (AI) has sprayed a vibrant message to people in all areas of life including the education field due to the easy access to vast information with a click in an autonomous way and enhancing the overall learning experience. This study provides an overview of the significance of AI applications, their role in education and where the practitioners are in the concurrent situation. Especially, it explores some of the AI approaches best practised, including personalised learning, adaptive learning, teaching evaluation, virtual classroom, and intelligent teaching. It also highlights some of the ethical and social implications of using AI in education, including issues related to privacy, equity, and the role of human teachers. I used the data published in various journals, and books, presented in academic forums in global and local contexts and analysed thematically. The study concluded that integrating AI in education with caution, considering the ethical implications and ensuring that all students have access to these new technologies will switch to an artificially led world where there is no boundary for accessing knowledge.